Legal Analysis of Disparities in Judges' Decisions in Criminal Assault Cases Resulting in Severe Injuries - Jumiati Jumiati; Kiki Kristanto; Louise Theresia (Eduvest - Journal of Universal Studies, 2026)
This research discusses the disparity of judges’ decisions in criminal assault cases resulting in severe injuries within the Indonesian criminal justice system. Sentencing disparity has become an important legal issue because differences in punishment for similar criminal acts may undermine legal certainty, justice, and public trust in the judiciary. The purpose of this study is to analyze the factors causing disparities in judges’ decisions and to examine the legal considerations used in imposing criminal sanctions, particularly in cases involving recidivist offenders and serious injuries. This study employed a normative juridical research method using conceptual and case approaches. Data were collected through literature studies involving statutory regulations, court decisions, legal doctrines, and relevant scientific journals. The analysis was conducted qualitatively using descriptive-analytical techniques to compare judicial considerations in similar cases. The findings indicate that disparities in sentencing are influenced by broad judicial discretion, differences in assessing aggravating and mitigating factors, and the absence of detailed sentencing guidelines. Recidivism status, severity of injuries, remorse, and restorative efforts significantly affected judicial decisions. The study concludes that sentencing disparity remains a fundamental issue in Indonesian criminal law enforcement. Therefore, clearer national sentencing guidelines, stronger judicial transparency, and more proportional consideration standards are necessary to ensure fairness, consistency, and accountability in criminal punishment.